(3GdeQGLYI GdNGQLjI (B:s (3GdeaGgje GdCSGSjI hCdjGJ GdJWHjb habG ddeYGjjQ GdeJYGQa YdjgG hGdeYGjjQ GdOhdjI (B/s - (3GdUHGf, eMeO SejQs; (3Ydi, YHOGdhgGH fUQs ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2002)
(3fXQjI GdeQGLYI hHjFI Yed GdeQGLYI ,WHjYI GdeQGLYI hXQhQI GjLGO fXQjI dgG eYGjQ GdeQGLYI GdeJYGQa YdjgG ,eSDhdjI GdeLJY GdNGQLj hCOGH GdSdhc Gdegfj ,eQGLYI GdejRGfjI hJbQjQ eQGbH GdMSGHGJ ,eQGLYI GdeNRhf eQGLYI OhQI GdJehjd JbOje eQGbH GdMSGHGJs
Keywords: (3GdMSGHGJs; (3GdeQGLYIs